2012
DOI: 10.1016/j.jneb.2011.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Theory of Planned Behavior to Explain Sugar-sweetened Beverage Consumption

Abstract: Objective To describe sugar-sweetened beverage (SSB) consumption, establish psychometric properties and utility of a Theory of Planned Behavior (TPB) instrument for SSB consumption. Methods This cross-sectional survey included 119 southwest Virginia participants. Respondents were majority female (66%), white (89%), ≤ high school education (79%), and averaged 41.4 (±13.5) years. A validated beverage questionnaire was used to measure SSB. Eleven TPB constructs were assessed with a 56-item instrument. Analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
98
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 26 publications
(33 reference statements)
3
98
1
Order By: Relevance
“…This finding is contrary to a previous study based on TPB for dietary behavior. 10 Because of the small sample size in the present study, this finding needs to be replicated by further research using a systematic, random sample of the entire study population in Korea and Japan. An important feature of this study is that it is the first application, to our knowledge, of the use of TPB-based variables to compare sweetness preference between Korean and Japanese children.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…This finding is contrary to a previous study based on TPB for dietary behavior. 10 Because of the small sample size in the present study, this finding needs to be replicated by further research using a systematic, random sample of the entire study population in Korea and Japan. An important feature of this study is that it is the first application, to our knowledge, of the use of TPB-based variables to compare sweetness preference between Korean and Japanese children.…”
mentioning
confidence: 77%
“…The survey variables were selected from those suggested in previous studies 10,11,21 and expert advice, and defined following implementation of a preliminary test involving 20 Korean children. We did not consider the socioeconomic status of participants from either country.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 (p. 502) Researchers have concluded that behavioral changes related to health and interventions have regularly found greater effects for theory-based interventions compared to those without a comprehensive theoretical basis. [32][33][34] Children look to their parents and caregivers to help encourage, support, and enable them to practice healthier eating habits. 25 The notion of self-identity also has been advanced as a possible predictor of behavior.…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
“…Perceived behavioural control can also have a direct impact on behaviour because performance of a behaviour not only depends on motivation, but also the individual control of the behaviour [18]. If an individual has limited control over an activity, the activity might not be implemented, even in the presence of strong motivational factors [19].The TPB has been applied to a wide variety of dietary behaviours including breakfast consumption, fruit and vegetable intake, eating behaviours, dieting and fat intake, along with many others [19]. Although it has been used quantitatively in various studies, it has rarely been used in qualitative studies targeting dietary behaviours.…”
mentioning
confidence: 99%